PENGARUH KEPEMIMPINAN SITUASIONAL DAN BUDAYA ORGANISASI TERHADAP MOTIVASI KERJA DAN KINERJA KARYAWAN - Fitria Nur Azizah (Jurnal Bisnis dan Manajemen, 2017)
The purpose of this study was toanalyze how much the situational leadership and organizational culture affects work motivation and employees performance at KAN Jabung Malang. The population in this study as many as 212 employees and a sample is used as much as 139 respondents. Sampling method using proportional non random sampling method. This study uses a quantitative approach with Path Analysis. The results showed that the situational leadership, organizational culture and work motivation had no significant effect on employee performance. Situational leadership and organizational culture have a significant effect on work motivation. Situational leadership and organizational culture does not significantly influence employee performance through work motivation. Based on these results, cooperatives need to unify understanding between leaders and employees, namely by paying attention to what is required of employees in terms of leadership style, organizational culture and work motivation in improving the performance of employees in order to achieve the same goal DOI : https://doi.org/10.26905/jbm.v4i1.1708